INOVASI PUPUK KERING DARI LIMBAH ORGANIK TPI INENGO, DESA HUANGOBOTU KABUPATEN BONE BOLANGO - Wila Rumina Nento; Shindy Hamidah Manteu; I Made Sudiarta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2025)
This community service activity aims to introduce an innovation in processing organic waste from fishery by-products at the Fish Auction Place (TPI) Inengo, Huangobotu Village, Bone Bolango Regency, into environmentally friendly and economically valuable nutrient-rich dry fertilizer. Organic waste generated from fish auction activities, such as bones, scales, fish skin, and entrails, has not been optimally managed, thus potentially causing environmental pollution and health problems for the surrounding community. Through a participatory approach, the service team carried out socialization, technical training, and assistance for community groups in Huangobotu Village, particularly the youth organization (karang taruna), regarding the process of converting waste into dry fertilizer. The production process was conducted using simple and easily applicable methods, including material collection, chopping, fermentation with microbial activators, drying, and packaging of the final product. The results of this activity indicated an increase in the community’s knowledge and skills in processing organic waste into useful products, as well as the potential to improve income through fertilizer sales. This innovation is expected to serve as a model for sustainable organic waste management in coastal areas, while also supporting environmentally friendly agricultural programs in Gorontalo. Abstrak Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkenalkan inovasi pengolahan limbah organik dari hasil samping perikanan di Tempat Pelelangan Ikan (TPI) Inengo, Desa Huangobotu, Kabupaten Bone Bolango menjadi pupuk kering bernutrisi yang ramah lingkungan dan bernilai ekonomis. Limbah organik yang dihasilkan dari aktivitas pelelangan ikan, seperti tulang, sisik, kulit ikan, dan jeroan, selama ini belum dikelola secara optimal sehingga berpotensi menimbulkan pencemaran lingkungan dan gangguan kesehatan masyarakat sekitar. Melalui pendekatan partisipatif, tim pengabdi melakukan sosialisasi, pelatihan teknis, serta pendampingan kepada kelompok masyarakat Desa Huangobotu dalam hal ini karang taruna tentang proses pengolahan limbah menjadi pupuk kering. Proses produksi dilakukan dengan metode sederhana yang mudah diterapkan, meliputi pengumpulan bahan, pencacahan, fermentasi dengan aktivator mikroba, pengeringan, dan pengemasan produk akhir. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan masyarakat dalam mengolah limbah organik menjadi produk yang bermanfaat serta berpotensi meningkatkan pendapatan melalui penjualan pupuk. Inovasi ini diharapkan menjadi model pengelolaan limbah organik di kawasan pesisir yang berkelanjutan, sekaligus mendukung program pertanian ramah lingkungan di Gorontalo.